A comparison of respiratory and peripheral muscle strength, functional exercise capacity, activities of daily living and physical fitness in patients with cystic fibrosis and healthy subjects. (October 2015) - Arikan, Hulya; Yatar, İlker; Calik-Kutukcu, Ebru; Aribas, Zeynep; Saglam, Melda; Vardar-Yagli, Naciye; Savci, Sema; Inal-Ince, Deniz; Ozcelik, Ugur; Kiper, Nural
Highlights: Peripheral muscle strength and exercise capacity decreases in cystic fibrosis. Performance in activities of daily living is adversely affected in cystic fibrosis. Physical fitness decreases in patients with cystic fibrosis compared to healthy. Glittre ADL-test can be used in patients with cystic fibrosis. Abstract: There are limited reports that compare muscle strength, functional exercise capacity, activities of daily living (ADL) and parameters of physical fitness of cystic fibrosis (CF) patients with healthy peers in the literature. The purpose of this study was to assess and compare respiratory and peripheral muscle strength, functional exercise capacity, ADL and physical fitness in patients with CF and healthy subjects. Nineteen patients with CF (mean forced expiratory volume in one second-FEV1 : 86.56 ± 18.36%) and 20 healthy subjects were included in this study. Respiratory (maximal inspiratory pressure-MIP and maximal expiratory pressure-MEP) and peripheral muscle strength (quadriceps, shoulder abductors and hand grip strength) were evaluated. Functional exercise capacity was determined with 6 min walk test (6MWT). ADL was assessed with Glittre ADL test and physical fitness was assessed with Munich fitness test (MFT). There were not any statistically significant difference in MIP, %MIP, MEP and %MEP values between two groups ( p  > 0.05). %Peripheral muscle strength (% quadriceps and shoulder abductors strength), 6MWT distance and %6MWT distance were significantly lower in patients with CF than those of healthy subjects ( p  < 0.05). Glittre ADL-test time was significantly longer in patients with CF than healthy subjects ( p  < 0.05). According to Munich fitness test, the number of bouncing a ball, hanging score, distance of standing vertical jumping and standing vertical jumping score were significantly lower in patients with CF than those of healthy subjects ( p  < 0.05). Peripheral muscle strength, functional exercise capacity, ADL performance and speed, coordination, endurance and power components of physical fitness are adversely affected in mild-severe patients with CF compared to healthy peers. Evaluations must be done in comprehensive manner in patients with CF with all stages.